Thermo-physical properties and high-temperature durability of reactive powder concrete (RPC) - Helmi, Masdar (2016)
The popular use of concrete, particularly in the construction industry, has continually challenged researchers to advance its performance to new levels. Research in this area has led to substantial ideas of reactive powder concrete (RPC) which is developed by controlling three main variables: composition, pressure during setting period, and post-set heat curing. A growing community of research has emerged to define the physical and mechanical properties of RPC, but to date few have focussed on the high temperature behaviour and aging effects after exposure to fireand that influence the durability of concrete. This research aimed to characterise the thermo-physical properties of RPC and to quantify the microstructural transformation caused by (i) high temperature curing, and (ii) fixed and cyclic high temperature exposure (at 28-day strength). The experimental work mainly used a RPC mixture and involved three defined stages. Firstly, the optimisation of RPC was investigated by analysing the mix composition and measuring the corresponding mechanical properties of RPC with variables such as heating rate, heating duration, and starting time of heating. Secondly, the transformation of microstructural properties was investigated with respect to the pre- and post-treatment conditions and included pore network evolution, elemental composition, and image analysis of the interfacial transition zone (ITZ). Thirdly, the response to high temperature exposure was analysed by focussing on the residual compressive strength and alteration of microstructural properties (after both static and cyclic temperature exposure of varying levels). The main findings are summarised as follows: (1) heat curing appears to have optimum impact (after casting) at a ramp rate of 50 °C/hr for 48 hours; (2) heat curing treatment induced some effects such as pore filling by tobermorite and xonotlite, with some dehydroxilation of C-S-H gel and Ca (OH)2; (3) the thermo-physical properties of RPC were all reduced following heat treatment/ exposure due to crack network progression; (4) after elevated temperature exposure, the compressive strength of RPC decreases due to differential shrinkage between the matrix and aggregate phases.